Mothers in the Spirit: A Pneumatic Reflection on Mary the Mother of the Church and Church Mothers in the Sanctified Tradition - Price, Andre L. (Journal of pentecostal theology, 2016)
Some Protestants consider Catholic Mariology to be problematic due to perceived excesses in the Catholic tradition. This theological reflection argues that church mothers in the sanctified tradition are a pentecostal variation of Catholic thought and understanding of Mary the Mother of Jesus. Particular attention is given to church mothers in the sanctified tradition and Mary the Mother of Jesus. The goals are to bring pentecostals and Catholics into dialogue around Mariology, to connect Pentecostal spirituality to the broader theological tradition, and to tell the story of an underrepresented group that is instrumental to the life of the church. Paying particular attention to Luke 1.26–38 and Acts 2.1–12. Special consideration is given to the commonalities between church mothers in the sanctified tradition and Mary the Mother of Jesus revolving around pneumatic themes. A pneumatic lens opens space to show the continuity between mothers in the essential areas of holiness, exemplars to their communities, and mothers of the Kingdom.